THE EFFECT OF BRAIN GYM TOWARDS CHANGES OF STRESS LEVELS IN GRADE VI CHILDREN DURING DISTANCE LEARNING - Nunik Purwanti; Annif Munjidah; Nur Masruroh; Hinda Novianti; Ardianti Fauziah Rochmah (STIKES Cendekia Utama Kudus, 2022)
In an academic environment, stress is something that often occurs by students, both consciously and unconsciously. Especially when there is a covid-19 pandemic where academic activities apply distance learning. Stress can occur due to the large workload, parental demands and lack of peer interaction. The purpose: To analyze the effect of brain exercise on changes in stress levels in children during distance learning at SD Darul Ulum Bungurasih. Method: Using a pre-experimental design with One Group Pre-test and Post-test, the population was 83 children with a sample size of 69 children from 28 grade V and 41 grade VI children. The sampling technique used random sampling (probability sampling) and group sampling (cluster sampling). The independent variable is brain exercise and the dependent variable is the change in stress levels in children during distance learning at SD Darul Ulum Bungurasih. The kueisoner used is PSS-10. Data analysis using Wilcoxon test. The results of data analysis obtained by the Wilcoxon test were p = 0.000 <0.05, meaning that there was an effect of brain exercise on changes in stress levels in children during distance learning at SD Darul Ulum Bungurasih. The conclusion of this study is that brain exercise is good for reducing stress levels in children and can be applied in school regularly and correctly. Keywords: Children, stress levels, brain gym